Topology optimisation for vat photopolymerization 3D printing of ceramics with flushing jet accessibility constraint - Liu, Jikai; Zhang, Chenghu; Zou, Bin; Li, Lei; Yu, Huangchao (Virtual and physical prototyping, 2024)
For vat photopolymerization 3D printing technology with high-viscosity ceramic slurry, the cleaning of residual uncured slurry presents a challenging task for lattice-based porous structures. Hence, this study contributes a multi-scale topology optimisation method for lattice-solid hybrid structures dedicated to ceramic vat photopolymerization 3D printing. A novel flushing jet accessibility constraint is proposed, aiming to effectively remove the residual uncured slurry after finishing the vat photopolymerization. Specifically, a multi-material interpolation for graded lattices and solid materials is introduced to form the fundamental of topology optimisation. Then, a series of filtering and projection operations are developed to ensure the accessibility of flushing waters to every location that may have residual ceramic slurry. Accordingly, a multi-scale topology optimisation mathematical model is established and solved with the adjoint sensitivities. 2D and 3D numerical examples are conducted to evaluate the effectiveness of the proposed method. Furthermore, a 3D printing experiment is performed to validate the full water jet accessibility of the optimised structural solution and one pillow bracket part is carried out as a practical application demonstration.